Counter-Intuitive Correlation: Does Emotional Intelligence Always Mitigate Language Anxiety? - Istiqamah Ardila; Rahmaniyah Rahmaniyah; Syairatul Aulia (Indonesian Journal Publisher, 2026)
Foreign language anxiety often hinders students performance, yet the role of emotional intelligence in mitigating this stress remains complex. This study aims to examine the levels of emotional intelligence (EI) and foreign language anxiety (FLA) among middle school students and determine the correlation and impact between these two variables. A quantitative correlational design was employed involving 58 students from two Indonesian middle schools. Data were collected using adapted emotional intelligence and language anxiety scales, then analysed using correlation and simple regression techniques. The findings show that most students possess average emotional intelligence (53.4) and experience mild anxiety (53.5). Statistical analysis reveals a surprising positive correlation (r = 0.259), indicating that higher emotional intelligence is associated with increased anxiety levels. The regression equation, Y= 70.241 + 0.639X, confirms that EI significantly contributes to the variance in students anxiety. In conclusion, this study suggests that emotional awareness in young learners does not automatically reduce anxiety and may instead heighten their sensitivity to language learning challenges. These insights encourage educators to develop more nuanced emotional support strategies in the classroom.